Penggunaan Metafora dalam Puisi William Wordsworth - Puspa Sari (FKIP, Universitas Lakidende Unaaha, 2015)
This study aims at identifying the types and functions of metaphores used in selected Wordsworth poems. It was a qualitative research and library method was used in collecting the data. The data of the study are the series of England poems of I, II, III, and IV. The data were analyzed descriptively based on the methatphore chategories. The findings suggested that there are three types of metaphore used in the four poems. They were: 1) antromorphic image, 2) animal image, 3) concrete image, and sinestesia image. In addition, the use of methahores functions 1) to balance inadequacy, 2) to express aesthetics, and 3) to avoid monotone.